Pengaruh Kompetensi Karyawan Dan Insentif Terhadap Stress Kerja Karyawan Pada PT. Putra Niaga Jaya - Yusuf Taufik; Wie Shi Wudjud (Jurnal of Management and Social Sciences, 2023)
This study aims to examine the effect of competence and incentives on the work stress of PT Poetra Niaga Jaya's employees. The importance of the discussion on human resource management (HRM) that humans are the most important element in all organizations, and the success of an organization to achieve its goals is largely determined by the ability to manage human resources precisely. Improved HR management will support the creation of effective employee behavior in carrying out tasks.The method used in this research is quantitative research by distributing questionnaires. The population of this research is all 58 employees of PT Poetra Niaga Jaya. Variables are measured with a Likert scale. The model of data analysis used to answer hypotheses is multiple regression.Based on the results of multiple linear regression testing competencies and incentives have a significant and significant effect on PT Poetra Niaga Jaya Employee Stress. Partial test results, the results of this study stated that Competence has a significant effect on Job Stress and Incentives also have a significant effect on Employee Stress at PT Poetra Niaga Jaya.